Effect of Microbiome Inoculation in Corn Crop (Zea mays) for Baby Corn and Forage Production on Growth and Biomass Ratio - Saputra, Arif Ragil; Indriani, Nyimas Popi; Mansyur, Mansyur (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
This study aims to determine the effect of microbiome inoculation on the growth and biomass ratio of corn crop-producing baby corn and forage. This research was conducted in the Ciparanje research field and Animal Food Plant Laboratory Faculty of Animal Husbandry, Padjadjaran University. The method used was an experimental method with a completely randomized design (CRD) consisting of six treatments and four replicates in each treatment. The treatments consisted of P1= BP4, P2= Probiotic LAB, P3= Mycofer (arbuscular mycorrhizal fungi), P4= BP4 + Mycofer, P5= LAB + Mycofer, P6= BP4 + LAB + Mycofer. There are five parameters observed, consisting of plant height every week, number of leaves, age of plant at tassel emergence, leaf to stem ratio (LSR), and shoot to root ratio. The data were then analyzed using Analysis of Variance (ANOVA), and if it showed significant results, it was continued with Duncan's further test. The results showed no significant effect of microbiome inoculation on, age of plant at tassel emergence and leaf to stem ratio. Significant results were obtained in the 9th-week plant height parameter (best in P5 at 158.25 cm), number of leaves (best in P5 at 15.75) and shoot to root ratio (best in P6 at 1.58). Overall, it can be concluded that microbiome inoculation can increase nutrient use efficiency and reduce inorganic fertilizers by as much as 50%, supporting environmentally friendly and sustainable agricultural and livestock practices.